Technological performance assessment innovation for elite-level snowboarding - Harding, J. (Griffith University, 2010)
This thesis focuses on the introduction of sport science and engineering techniques for performance assessment in competitive half-pipe snowboarding. Performance data was collected over three winter seasons from 2006 to 2008 including a Winter Olympic Games and was used to establish objective key performance indicators (KPI`s) that account for a large percentage of the variance in subjectively judged competition scores. These findings were then applied to customise wearable sensor technology to develop an automated performance feedback system suitable for everyday use. This system was subsequently used to run the first electronically judged half-pipe snowboard competition in the world. Furthermore, the impact of sport science and new technology on the sport of snowboarding was assessed, allowing the snowboarding community to articulate their interests in forums that convey influence. This thesis establishes that it is no longer a question of whether the theoretical framework or technological innovation is there to automatically provide objective, performance-based information for halfpipe snowboarding but rather if and how coaches, athletes and competition judges plan to utilise such capabilities. In addition, this thesis recommends that any further development and integration of such concepts be conducted in close association with core community members and be ultimately controlled from within the sport.